2018
DOI: 10.15666/aeer/1606_80938103
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF HORMONE (17α-METHYLTESTOSTERONE, 17β-ESTRADIOL) USAGE ON DEVELOPMENT, SEX INVERSION AND PIGMENTATION OF ELECTRIC YELLOW CICHLID (Labidochromis caeruleus FRYER, 1956)

Abstract: This research was designed in order to examinate the effects of 17α-methyltestosterone and 17β-estradiol hormone use on the development, growth performance, survival, sex ratio and coloration of the electric yellow cichlid (Labidochromis caeruleus Fryer, 1956). Seven different groups were designed in the study. While no hormones were added to the control diet, 6 different rates of hormones were added to the other groups. Cichlid mean weight was determined as 0.64±0.01 g, were stored such that three replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Fish groups fed 17α-MT hormone had a better growth rate. These results are in agreement with the studies on Labidochromis caeruleus (see Karsli et al 2018), Oreo-chromis andersonii (see As et al 2012), O. niloticus (see Greisy and Gamal 2012;Ajiboye et al 2015), and Trichogaster lalius (see Biswas et al 2014). However, other studies reported that the hormone treatment negatively affected growth and development in a dose-dependent manner in zebra cichlids (George and Pandian 1996), Betta splendens (see Kirankumar and Pandian 2002), and O. niloticus (see Sreenivasa and Prabhadevi 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Fish groups fed 17α-MT hormone had a better growth rate. These results are in agreement with the studies on Labidochromis caeruleus (see Karsli et al 2018), Oreo-chromis andersonii (see As et al 2012), O. niloticus (see Greisy and Gamal 2012;Ajiboye et al 2015), and Trichogaster lalius (see Biswas et al 2014). However, other studies reported that the hormone treatment negatively affected growth and development in a dose-dependent manner in zebra cichlids (George and Pandian 1996), Betta splendens (see Kirankumar and Pandian 2002), and O. niloticus (see Sreenivasa and Prabhadevi 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, it has been reported that the 17α-MT hormone increased pigmentation which has a positive impact on coloration in B. splendens and Xiphophorus hellerii (see Jessy and Warghese 1987). When the physical color analysis results of the Karsli et al (2018) study on electric yellow cichlid were evaluated, it was determined that the best coloration was obtained in 17α-MT groups, similar to this study. In contrast to these studies, it was reported that 17α-MT supplementation for 28 days did not affect coloration in Xiphophorus hellerii (see Koshio et al 1993;Yanong et al 2006).…”
Section: Discussionsupporting
confidence: 76%
“…Significant difference in survival was found between groups, T9 and T6, compared to other experimental groups (T3 and T0; p < .05). In studies conducted with cichlid fish, weight gain, survival rates varied between 53.3% and 100% (Karslı et al, 2018; Yeşilayer et al, 2020; Yılmaz & Ergün, 2011). Purslane supplemented groups had highest relative survival rate, whereas the control fish group was with the lowest relative survival.…”
Section: Discussionmentioning
confidence: 99%
“…In ornamental fish farming, growth, reproduction and coloration of fish are primarily dependent upon adequate supply of feed ingredients and additives. For this reason, studies on aquarium fish diets have been focused on using natural ingredients (Yeşilayer, Aral, et al, 2011) and additives (Karsli et al, 2016, 2018; Yeşilayer et al, 2020; Yiğit et al,2019) to achieve better results for successful aquaculture practices considering reproduction and coloration parameters, survival rate and disease resistance. Colour is one of the major factors which determine the price of the ornamental fish in the world market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation